Autoantibodies and damage in patients with idiopathic inflammatory myopathies: A longitudinal multicenter study from the MYONET international network - Espinosa-Ortega, Fabricio; Lodin, Karin; Dastmalchi, Maryam; Vencovsky, Jiri; Diederichsen, Louise P; Shinjo, Samuel Katsuyuki; Danieli, Maria Giovanna; Selva-O'Callaghan, Albert; de Visser, Marianne; Griger, Zoltan; Ceribelli, Angela; Gómez-Martin, Diana; et al. (Seminars in arthritis and rheumatism, 2024)
OBJECTIVE: To study the trajectories of changes in damage over time and explore associations with autoantibody defined subgroups using a large international cohort of patients with idiopathic inflammatory myopathies (IIM). METHODS: Data from the MYONET registry, including patients who were tested for autoantibodies and had at least one assessment of damage using the Myositis Damage Index (MDI), were analyzed. Patients were sub-grouped according to their autoantibody profiles (myositis-specific, myositis-associated, or seronegative). The index date was defined as the time point for the first registered MDI assessment. The longitudinal trajectories of damage with autoantibody status as the main predictor were analyzed using linear mixed models. RESULTS: A total of 757 adult patients were included in this study. Each year of disease duration since diagnosis had an estimated MDI score increase of 0.16 units for the seronegative group (reference). Compared with the seronegative group as reference, patients with dermatomyositis-specific autoantibodies developed less damage per year of follow-up since diagnosis (average 0.08 less score, P = 0.04), whereas patients with anti-PM/Scl autoantibodies developed more damage per year of follow-up since diagnosis (average 0.28 higher score, P = 0.03) independent of sex and age at diagnosis. The seronegative subgroup and the immune-mediated necrotizing myopathy autoantibody subgroup had the strongest correlation between severity of muscle damage and HAQ-DI scores at five years of follow-up, rho=0.84, P < 0.001 and rho=0.72, P < 0.001, respectively. CONCLUSION: Our study is the first to describe patterns and trajectories of change in damage over time in relation to autoantibody defined subgroups in a large international multicenter cohort of patients with IIM. Patients with anti-PM/Scl scored a greater extent of damage, whereas patients with dermatomyositis-specific antibodies had less damage than seronegative patients. Severity in muscle damage had moderate to strong correlation with functional disability among the IMNM and seronegative subgroups with lower correlations for the other subgroups. These findings suggest that autoantibodies may be useful predictors of long-term damage.
Keywords: Inflammatory myopathies; dospělí; Dermatomyositis; Female; autoprotilátky; Adult; ženské pohlaví; longitudinální studie; Registries; Organ damage; lidé; stupeň závažnosti nemoci; myozitida; Male; progrese nemoci; Aged; Autoantibodies; Disease Progression; Myositis; lidé středního věku; registrace; senioři; mužské pohlaví; Severity of Illness Index; Middle Aged; dermatomyozitida; Longitudinal Studies; Humans